Characterization and Stability of Multimixed Additive-Quartic Mappings: A Fixed Point Application. (12th November 2021) - Bodaghi, Abasalt; Alias, Idham Arif; Mousavi, Lida; Hosseini, Sedigheh
Abstract : In this article, we introduce the multi-additive-quartic and the multimixed additive-quartic mappings. We also describe and characterize the structure of such mappings. In other words, we unify the system of functional equations defining a multi-additive-quartic or a multimixed additive-quartic mapping to a single equation. We also show that under what conditions, a multimixed additive-quartic mapping can be multiadditive, multiquartic, and multi-additive-quartic. Moreover, by using a fixed point technique, we prove the Hyers-Ulam stability of multimixed additive-quartic functional equations thus generalizing some known results.